Praxeological tales as an innovative media product for fostering successful personalities in primary school pupils (Educational Dimension, 2024)
This study aims to substantiate the technology of forming a successful personality in primary school pupils through implementing media education, focusing on using praxeological tales. The research methods include theoretical analysis of literary sources, modelling, and empirical techniques such as observation, questionnaires, surveys, and experiments. The results show that praxeological tales, which reflect the basic rules and factors of achieving success, can be an effective, innovative media product in shaping successful pupils. The proposed technology model incorporates praxeological tales and other media education tools and techniques. An experimental study involving control and experimental groups of primary school pupils demonstrated that the percentage of children with a high level of successful personality development increased from 9.6% to 23.1% in the experimental groups. In contrast, the percentage of low levels decreased from 42.3% to 20.2%. The findings suggest that forming successful personalities in primary school through media education using praxeological tales can help increase pupils' media literacy, develop key life competencies, and prepare children for future self-realisation.
Keywords: primary school pupils; media education; praxeological tales; educational technology